Study On The Anthropometric Data Of Ergonomic On Existing Minbar Designs At Johor’s Mosques - Ahmad Nasir, Mohamad Nursyafiq; Tami, Hannifah; Adnan, Nor Azizah (Recent Trends in Civil Engineering and Built Environment, 2021)
The minbar, which is located in the prayer hall, is one of the most prominent mosque features. Minbar is available in a variety of heights, widths, and lengths. The relation between the minbar and the volume of the prayer hall is frequently overlooked, lowering the visual aesthetics value of the interior space. The golden ratio is the gold standard in interior design when it comes to design choices and is crucial in creating the optimal product design. The effective usage of this ratio is widely thought to be an effective approach to develop amazing design. As a result, the aim of this study is to learn how to apply the Golden Ratio concept to the minbar applying mathematical ratios to represent aesthetic value and internal proportion. Future engineers and architects should be more aware of the ergonomic aspect in the design of the minbar that provide the user with comfort and safety. This study used a golden spiral template made with AutoCAD software to find the best height of the existing minbar design that is adequate for the length of the prayer hall and to calculate the appropriate ratio of anthropometric factors. The ratio is produced when a/b equals a+b/a, resulting in both equaling 1.618. As a case study, ten existing minbars were chosen from mosques in the state of Johor. The study’s findings focused on reading the width, height, and depth measurements on the minbar’s front elevation. In comparison to the other ten pieces, a percentage of 30% (3 minbar) met the best proportion. As there is no tangling of lines between golden ratio influencing items on a high platform floor, width and height, the 70% pulpit does not match the correct proportions. In the pulpit design process, the golden ratio contributes in the creation of beauty and harmony. In light of the influence, the proportion of mathematics linked with user convenience and aesthetic appeal. The elegant and impeccable design contributes to a safe and comfortable minbar features.